Agricultural sector of Prykarpattya economic (1965 - 1991 years): achievements and miscalculations - Oleg Malyarchuk (Cхід, 2013)
In this article author tries to highlight the evolution of  agricultural policy  of the Party and Soviet power in a definite period, new approaches in solving urgent problems. To overcome crisis anticipated by organizational and economic and financial methods: increasing capital investment, strengthening the technical base of kolhozes and state farms, the correct placement of communists in the decisive areas of work, increasing purchasing prices for agricultural products, intensification of agriculture, specialization of production, new planning system, introduction of the guaranteed payment to collective farmers, creation of agricultural  enterprises